1970
DOI: 10.2136/sssaj1970.03615995003400020031x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Macro‐ and Micronutrients in Soil Profiles Developed on Lithosequences and under Biosequences in Northern Greece

Abstract: The status and the distribution of the macro‐ and certain of the micronutrients in selected soil profiles developed on different parent materials such as granite, quartz diorite, dacite, and marble and under varying cover such as spruce (Picea excelsa L.), scotch pine (Pinus silvestris L.), beech (Fagus silvatica L.), and grasses were investigated.The results presented in a series of graphic illustrations indicate a distinct tendency for an accumulation of the nutrient supply in the uppermost horizons of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In FD soils there is generally a steady fall in extractable content of most trace elements from the surface downwards (e.g. Swaine & Mitchell 1960;Apostolakis & Douka 1970;Follett & Lindsay 1970). In poorly drained soils, on the other hand, there is often, in addition to high extractable levels of some elements at the surface, a marked increase in extractability, occasionally of quite different elements, in the lower gleyed horizons (Swaine & Mitchell 1960).…”
Section: Forms Of Occurrence Of Mobilised Trace Elementsmentioning
confidence: 99%
“…In FD soils there is generally a steady fall in extractable content of most trace elements from the surface downwards (e.g. Swaine & Mitchell 1960;Apostolakis & Douka 1970;Follett & Lindsay 1970). In poorly drained soils, on the other hand, there is often, in addition to high extractable levels of some elements at the surface, a marked increase in extractability, occasionally of quite different elements, in the lower gleyed horizons (Swaine & Mitchell 1960).…”
Section: Forms Of Occurrence Of Mobilised Trace Elementsmentioning
confidence: 99%
“…Therefore, a more strongly developed profile would be expected from coniferous forests than deciduous forests in similar environments during the same length of time. Apostolakis and Douka (1970) found that available soil phosphorus differs little among tree species, but is in greater quantities than prairie soils. Albaqualfs are more strongly developed and have higher accumulations of available phosphorus than Aquolls (Smeck and Runge, 1971;Tembhare, 1973).…”
mentioning
confidence: 96%